The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1073/pnas.78.5.2972
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury(II) binding to single-stranded and duplex DNA: complexes formed are distinguishable by optical detection of magnetic resonance spectroscopy.

Abstract: Binding of CH3Hg(II) to duplex and singlestranded calf thymus DNA leads to an external heavy atom effect that is associated with the formation ofcomplexes directly with the purine and pyrimidine bases. When CH3Hg(II) is added at a concentration insufficient to cause denaturation, clearly distinguishable optical detection of magnetic resonance spectra are observed from the duplex and single-stranded DNA complexes. Comparison of the dominant signals with those observed from CH3Hg(II) complexes of model mononucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Also, addition of Hg 2+ to a 1 μM solution of FMN causes a linear decrease in I PL with increasing Hg 2+ concentration (the red trace of Figure e), whereas addition of this metal ion to a 10 μM FMN solution results in an exponential decrease in the PL intensity. Moreover, the fact that addition of a 10-fold excess of Hg 2+ , which should promote predominant formation of the 1:1 complex, does not completely quench the PL of FMN suggests that, along with chemical bonding with FMN, Hg 2+ might be involved in modulation of the aggregation state of FMN. , Hg­(II) is known to bind with bases of DNA and RNA, resulting in quenching of nucleotide PL owing to the heavy-atom effect . This is the primary reason for quenching of FMN PL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, addition of Hg 2+ to a 1 μM solution of FMN causes a linear decrease in I PL with increasing Hg 2+ concentration (the red trace of Figure e), whereas addition of this metal ion to a 10 μM FMN solution results in an exponential decrease in the PL intensity. Moreover, the fact that addition of a 10-fold excess of Hg 2+ , which should promote predominant formation of the 1:1 complex, does not completely quench the PL of FMN suggests that, along with chemical bonding with FMN, Hg 2+ might be involved in modulation of the aggregation state of FMN. , Hg­(II) is known to bind with bases of DNA and RNA, resulting in quenching of nucleotide PL owing to the heavy-atom effect . This is the primary reason for quenching of FMN PL.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the fact that addition of a 10-fold excess of Hg 2+ , which should promote predominant formation of the 1:1 complex, does not completely quench the PL of FMN suggests that, along with chemical bonding with FMN, Hg 2+ might be involved in modulation of the aggregation state of FMN. 48,49 Hg(II) is known to bind with bases of DNA and RNA, 50 resulting in quenching of nucleotide PL owing to the heavy-atom effect. 51 This is the primary reason for quenching of FMN PL.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Higher generation PAMAMs possessed more primary amine groups on the surfaces available for DNA immobilization, and hence enhanced removal capacities and efficiencies were expected. Regarding MeHg(I), however, it coordinated most strongly at the N3 site of thymine and somewhat less tightly at the N1 site of guanine, which were involved in Watson‐Crick base pairing of the DNA duplex. Therefore, coordination between MeHg(I) and normal‐structured DNA duplex was theoretically not very strong.…”
Section: Resultsmentioning
confidence: 99%
“…In support of these conclusions, at the in vivo morphologic studies of Moller-Madsen ( 1990 , 1991 ) in which it is shown that CH3Hg+ deposits extensively throughout the CNS of rodents after administration via intraperitoneal and oral routes. It can be postulated that, upon permeation of barriers, the final common pathway underlying the mechanism of intracellular CH3Hg+ toxicity is genotoxicity (Grotto et al 2009 ) due to its covalent binding of DNA (Maki and Ott 1981 ) and disruption of transcription pathways, leading to cellular instability and cell death. Exposure to significant doses of CH3Hg+ during pregnancy have resulted in offspring with significant neurodevelopmental abnormalities as was the case at Minamata Bay (Eto et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%